2017
DOI: 10.18203/2320-1770.ijrcog20175117
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of ectopic pregnancy at a tertiary care centre

Abstract: Background: Ectopic pregnancy is a global problem and is the most common life-threatening emergency in early pregnancy leading to significant morbidity and fetal loss. It occurs in variable presentations. The rate of ectopic pregnancies has increased from 0.5% in 1970 to 2% today. The aim of this study was to determine the incidence, clinical presentation, risk factors, treatment, and morbidity and mortality associated with ectopic pregnancy.Methods: The present retrospective study was conducted over a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 4 publications
6
15
2
Order By: Relevance
“…In postpartum period, edematous, congested and friable tube increases the chance of incomplete tubal occlusion resulting in ectopic implantation. A history of infertility preceded 8.88% of the cases synchronous with 6.25%, 7%, 8% of Mehta A, Sudha VS, Ganitha et al 13,16,17 Ovulation induction history was found in 6.6% of the study subjects comparable to 1.25%, 4% of Mehta A, Shetty VH et al respectively. 16,18 Hormonal alterations caused by clomiphene and other ovulation induction agents may predispose to tubal implantation.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…In postpartum period, edematous, congested and friable tube increases the chance of incomplete tubal occlusion resulting in ectopic implantation. A history of infertility preceded 8.88% of the cases synchronous with 6.25%, 7%, 8% of Mehta A, Sudha VS, Ganitha et al 13,16,17 Ovulation induction history was found in 6.6% of the study subjects comparable to 1.25%, 4% of Mehta A, Shetty VH et al respectively. 16,18 Hormonal alterations caused by clomiphene and other ovulation induction agents may predispose to tubal implantation.…”
Section: Resultsmentioning
confidence: 72%
“…Prior ectopic history was elicited in 4.44% of cases analogous to 3.75%, 4%, 4.2% of Mehta A, Shalini Kumari, S Tahmina et al 12,16,27 Tubal corrective surgery was documented in 4.44% of the study subjects which corresponds to 3.29%, 4%, 5.7% of Li, Karmakar, Assouni Mindjah YA et al respectively. 15,23,28 Use of medical abortifacients was documented in 4.44% of our patients parallel to 9.7% of Shetty KS et al 22 The overall risk of rupture of EP by OTC abortifacient is as high as 1.9% to 6.5% as demonstrated in studies by Sarojini and Kavina S et al 29,30 There is a dire need to institute an ultrasound mandatory before medical abortion, and bring in legislation seeking a protocol on the sale of MTP pills over the counter.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations